Web-based support for individuals with type 2 diabetes - a feasibility study - Marina Taloyan; Meybod Kia; Fahimeh Lamian; Magnus Peterson; Elisabeth Rydwik (BMC, 2021)
Abstract Background Self-care is one of the cornerstones in the treatment of type 2 diabetes. Patients with type 2 diabetes struggle to maintain acceptable levels of blood sugar, blood pressure and lipids, the fundamental for the prevention of macro- and microvascular as well as neuropathic complications. The primary aim of the study was to evaluate the feasibility and describe patients' and caregivers' experiences of using the web- and smartphone-based system Triabetes. The secondary aim was to investigate if the use of the system could improve patients' clinical outcomes. Methods Feasibility was assessed with describing recruitment rate and the participant´s views of using the system. Laboratory and anthropometry data were also collected. Results The study showed that recruitment of patients to participate in the intervention was limited and compliance to the study protocol was low. A majority of the patients stated that the system was easy to get an overview of and that the system motivated them and made it easier and fun to handle lifestyle habits. A secondary finding of the study was that there was a significant lowering of LDL values. Conclusions Feasibility in terms of recruitment rate was low. The participants agreed that the application overall was useful but suggested several improvements. Summarized lessons learned from this study are following: (1) we need more knowledge about what motivates a person to use a digital tool for a longer period of time; (2) the tool must be easy and less time consuming to use; (3) the technical structure needs to be improved and automatic recording of data must be improved.